ZINGIBERACEAE ETNOBOTANY AS A TRADITIONAL TREATMENT INGREDIENT FOR THE MANDAILING TRIBE IN VILLAGES AROUND THE BATANG GADIS NATIONAL PARK AREA, MANDAILING REGENCY NATAL - Sakinah, Indah; Nasution, Aswarina (JURNAL BIOSAINS, 2023)
ABSTRACKThis study aims to uncover and document belief systems, local knowledge systems, practice of using plants and culturally important values or ICS of plants of the Zingiberaceae family which are used as ingredients for traditional medicine by the Mandailing Tribe in villages around the Batang Gadis National Park area, Mandailing Natal Regency. The research location is in 2 villages around the Batang Gadis National Park, Mandailing Natal Regency. The research method is qualitative and quantitative. Data was collected through semi-structured interviews, participatory observation, documentation, focus group discussions, collection of plant samples and making herbarium. The results showed that there were 10 species of plants from the Zingiberaceae family used as traditional medicine by the Mandailing Tribe. The most widely used species is turmeric or hunik ( Curcuma dometica Val.). Turmeric is believed to cure 8 kinds of diseases. The rhizome organ is the organ that is most widely used with a percentage of 75%. The practice of using plants by the Mandailing Tribe with the most processing method is boiling as many as 10 plant species with a percentage of 35.71% and the most using method by drinking as many as 10 plant species with a percentage of 62.5%. Plants with a very high category of cultural importance or ICS are found in turmeric or hunik ( Curcuma dometica Val.) with an ICS value of 150, ginger or pegeh ( Zingiber officinale Roscoe. ) and red ginger or pegeh narara (Zingiber officinale var. Rubrum) with an ICS value of 120. Keywords: Traditional Medicine, Belief system, Local knowledge, Utilization practice, ICS